2021
DOI: 10.1016/j.jns.2021.117308
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility-weighted imaging reveals cerebral microvascular injury in severe COVID-19

Abstract: We evaluated the incidence, distribution, and histopathologic correlates of microvascular brain lesions in patients with severe COVID-19. Sixteen consecutive patients admitted to the intensive care unit with severe COVID-19 undergoing brain MRI for evaluation of coma or neurologic deficits were retrospectively identified. Eleven patients had punctate susceptibility-weighted imaging (SWI) lesions in the subcortical and deep white matter, eight patients had >10 SWI lesions, and four patients had lesions involvin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 22 publications
2
73
0
1
Order By: Relevance
“…The lesions had a predilection site subcortically and in deep white matter. They also showed radiological–pathological correlates of these microlesions, which included red blood cell extravasation, ischemia, deficiency, but not loss of axons and myelin, and microglial response [ 19 ]. Our patients did not have lesions in the corpus callosum, which may be a sign of a bad clinical picture and a worse clinical outcome [ 16 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lesions had a predilection site subcortically and in deep white matter. They also showed radiological–pathological correlates of these microlesions, which included red blood cell extravasation, ischemia, deficiency, but not loss of axons and myelin, and microglial response [ 19 ]. Our patients did not have lesions in the corpus callosum, which may be a sign of a bad clinical picture and a worse clinical outcome [ 16 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…They also showed radiological–pathological correlates of these microlesions, which included red blood cell extravasation, ischemia, deficiency, but not loss of axons and myelin, and microglial response [ 19 ]. Our patients did not have lesions in the corpus callosum, which may be a sign of a bad clinical picture and a worse clinical outcome [ 16 , 19 ]. Significant consequences and pathological changes after infection remained on all organs, especially on the lung parenchyma [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst these disorders of coagulation and endothelial integrity represent potential drivers of large vessel cerebrovascular disease, they also raise the possibility that impairment of the microvasculature might be involved in some of the less clear-cut neurological presentations, such as prolonged disorders of consciousness (including akinetic-mutism states) [63,[100][101][102], myoclonus (a relatively common complication with over 50 cases reported in the literature, which is seemingly unrelated to hypoxic ischaemic brain injury [103]), or even on the long-term cognitive outcomes of those who recover. Indeed, neuroimaging studies have commonly described cerebral microhaemorrhages occurring in those with severe COVID-19, reminiscent of microangiopathic disorders such as amyloid and hypertensive angiopathies [100,104,105], a phenomenon borne out in pathology series [32,75,100,106]. As would be expected in a disorder of the endothelium, similar microvascular changes have been described in multiple organ systems [107], and it has even been suggested that this process might be the cause of the mononeuritis multiplex seen in a substantial minority of survivors of severe COVID-19 [108].…”
Section: Neurovascular and Thromboembolic Diseasementioning
confidence: 99%
“…It is increasingly evident that SARS-CoV-2 is not only neurotropic, but is associated with a much broader spectrum of acute and atypical neurological syndromes and manifestations than prior infections, particularly those involving β-coronaviruses (Bohmwald et al, 2018;Desforges et al, 2019;Ellul et al, 2020;Iadecola et al, 2020;Koralnik and Tyler, 2020;Paterson et al, 2020). Severe acute neurological events observed in COVID-19 have included ischemic stroke, intracranial hemorrhage, diffuse encephalopathy, encephalitis and neuromuscular disorders (Alquisiras-Burgos et al, 2020;Lee et al, 2020;MacLean et al, 2020;Conklin et al, 2021). Neurocognitive symptoms and dysfunction of various severities have also become increasingly recognized as potential consequences of SARS-CoV-2 infection (Levine et al, 2020;Graham et al, 2021;Taquet et al, 2021).…”
Section: Introductionmentioning
confidence: 99%